2004
DOI: 10.1002/elps.200305822
|View full text |Cite
|
Sign up to set email alerts
|

Forensic DNA typing by capillary electrophoresis using the ABI Prism 310 and 3100 genetic analyzers for STR analysis

Abstract: DNA typing with short tandem repeat (STR) markers is now widely used for a variety of applications including human identification. Capillary electrophoresis (CE) instruments, such as the ABI Prism 310 and ABI 3100 Genetic Analyzers, are the method of choice for many laboratories performing STR analysis. This review discusses issues surrounding sample preparation, injection, separation, detection, and interpretation of STR results using CE systems. Requirements for accurate typing of STR alleles are considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
132
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(141 citation statements)
references
References 63 publications
0
132
0
9
Order By: Relevance
“…3,7,8 The use of fluorescence-based approaches allows performing large-scale human genetic tests and significantly reduces contamination because of keeping laboratory microtubes closed after PCR amplification. Accordingly, we checked the possibility of polymorphic Alu allelic discrimination by means of real-time PCR with Sybr Green dye and dissociation curves analysis using two primer pairs from our set.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3,7,8 The use of fluorescence-based approaches allows performing large-scale human genetic tests and significantly reduces contamination because of keeping laboratory microtubes closed after PCR amplification. Accordingly, we checked the possibility of polymorphic Alu allelic discrimination by means of real-time PCR with Sybr Green dye and dissociation curves analysis using two primer pairs from our set.…”
Section: Resultsmentioning
confidence: 99%
“…Many methodological approaches are used at the second stage, most of them involving precise determination of PCR products' length by PAGE or capillary electrophoresis with fluorescent labeling of analyzed DNA fragments, as well as quantitative real-time PCR, MALDI or microarray technology. [8][9][10] Although the latter methods are usually automated and have become a routine procedure, they still remain expensive because of the use of special facilities and fluorescent dyes. In the past decade, progress in human genome sequencing and methods of comparative genomics resulted in the identification of a new type of MGMs based on retroelement (RE) insertion polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Butler et al [89] have recently reported on sample preparation, injection, separation, detection, and interpretation of STR results using the widely used ABI prism 310 and 3100 genetic analyzers [89].…”
Section: Forensic Dna and Rna Analysismentioning
confidence: 99%
“…Additionally, electrophoresis-based methods only differentiate genotypes of length polymorphisms, while nucleotide variations such as single nucleotide polymorphisms (SNPs) in the flanking sequences of a repeat motif cannot be detected. Therefore, more potentials of the marker system have been restrained by the approaches to analyze the markers (Butler et al, 2004;Butler, 2007;Pascali et al, 2012). Thus, there is an urgent for new STR genotyping approaches.…”
Section: Introductionmentioning
confidence: 99%